2016
DOI: 10.1007/s11205-016-1402-6
|View full text |Cite
|
Sign up to set email alerts
|

Quadrilateral Relationship Between Information and Communications Technology, Patent Applications, Research and Development Expenditures, and Growth Factors: Evidence from the Group of Seven (G-7) Countries

Abstract: The quadrilateral relationship between information and communications technology (ICT), patent applications, research and development expenditures and specific growth factors examine to formulate the broad-based growth policies in the context of Group of seven (G-7) countries, over the period of 1995-2013. The ICT variables are explained by internet users, mobile cellular subscriptions and high-technology exports; while research and development (R&D) variables include R&D expenditures and researchers in R&D. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Considering the economic growth driven by innovations and knowledge, the level of economic freedom is not determining, contrary to the conclusions of Goel & Saunoris (2017). Similarly, it does not matter whether residential or non-residential patent applications predominate in the economy, unlike shown by Khan et al (2017). What determines the effect of innovation and knowledge is the level of technological sophistication, which is closely related to the level of investment in R&D and the production level of an economy.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Considering the economic growth driven by innovations and knowledge, the level of economic freedom is not determining, contrary to the conclusions of Goel & Saunoris (2017). Similarly, it does not matter whether residential or non-residential patent applications predominate in the economy, unlike shown by Khan et al (2017). What determines the effect of innovation and knowledge is the level of technological sophistication, which is closely related to the level of investment in R&D and the production level of an economy.…”
Section: Resultsmentioning
confidence: 87%
“…We derived the level of technological sophistication from the Technology Index (TI) variable, which we constructed using the Min-Max normalisation method from six variables retrieved from the World Bank database, namely Fixed Telephone Subscriptions (per capita), Mobile Cellular Subscriptions (per capita), Electric Power Consumption (kWh per capita), Fixed Broadband Subscriptions (per capita), High-Technology Exports (per capita, current USD), and Individuals Using the Internet (% of the population). These or similar variables are commonly used as measures of the technological sophistication of the country (e.g., Hasan & Tucci, 2010; Khan et al, 2017;Pradhan et al, 2017). This choice was inspired by Kim et al (2012), who identified a varying degree of contribution of innovations to growth because of differences in countries' technological capabilities.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…In their works Russian and foreign scientists [4][5][6][7][8][9][10][11][12] have proved that innovative technologies are the main component of the competitiveness of both an enterprise and a country. PJSC ROSNEFT pays special attention to the innovation and the introduction of breakthrough technologies in production.…”
Section: Innovative Activity Of Pjsc Rosneftmentioning
confidence: 99%
“…The BRICS countries (Brazil, Russia, India, China, and South Africa) represent a diverse group of developing economies characterized by rapid technological advancements, varying levels of growth, and governance and institutional development. They often work together to address economic challenges, promote trade, and collaborate on global issues like climate change, security, and development (Khan, et al, 2017). As these nations strive for sustained economic growth and development, the interplay between artificial intelligence (AI) investment, governance, and their impact on human well-being (human development) becomes a topic of significant interest and importance.…”
Section: Introductionmentioning
confidence: 99%